Find the general solution of the equation $ an(x) = cot(2x) $ on the unit circle
Answer 1
To solve the equation $ \tan(x) = \cot(2x) $ on the unit circle, we start by expressing $ \cot(2x) $ in terms of $ \tan(2x) $:
$ \cot(2x) = \frac{1}{\tan(2x)} $
The equation becomes:
$ \tan(x) = \frac{1}{\tan(2x)} $
Using the double-angle identity for tangent:
$ \tan(2x) = \frac{2 \tan(x)}{1 – \tan^2(x)} $
Substitute this back into the equation:
$ \tan(x) = \frac{1}{\frac{2 \tan(x)}{1 – \tan^2(x)}} $
Simplify the equation:
$ \tan(x) = \frac{1 – \tan^2(x)}{2 \tan(x)} $
Rearrange the equation:
$ 2 \tan^2(x) = 1 – \tan^2(x) $
Combine like terms:
$ 3 \tan^2(x) = 1 $
Solve for $ \tan(x) $:
$ \tan(x) = \pm \frac{1}{\sqrt{3}} $
Therefore, the general solution on the unit circle is:
$ x = n\pi + (-1)^n \frac{\pi}{6} $ where $ n $ is an integer.
Answer 2
To solve the equation $ an(x) = cot(2x) $, rewrite $ cot(2x) $:
$ cot(2x) = frac{1}{ an(2x)} $
Then:
$ an(x) = frac{1}{frac{2 an(x)}{1 – an^2(x)}} $
Simplify:
$ an(x) = frac{1 – an^2(x)}{2 an(x)} $
Which leads to:
$ 2 an^2(x) = 1 – an^2(x) $
Combining terms:
$ 3 an^2(x) = 1 $
Solving for $ an(x) $:
$ an(x) = pm frac{1}{sqrt{3}} $
Thus, the solution is:
$ x = npi + (-1)^n frac{pi}{6}, n in mathbb{Z} $
Answer 3
Rewriting the equation $ an(x) = cot(2x) $ gives:
$ an(x) = frac{1}{ an(2x)} $
Using the identity:
$ an(2x) = frac{2 an(x)}{1 – an^2(x)} $
We obtain:
$ an(x) = frac{1 – an^2(x)}{2 an(x)} $
Which simplifies to:
$ an(x) = pm frac{1}{sqrt{3}} $
So the solution is:
$ x = npi + (-1)^n frac{pi}{6} $
Start Using PopAi Today